Drought stress in ‘Shine Muscat’ grapevine: Consequences and a novel mitigation strategy–5-aminolevulinic acid - Yang, Yuxian; Xia, Jiaxin; Fang, Xiang; Jia, Haoran; Wang, Xicheng; Lin, Yiling; Liu, Siyu; Ge, Mengqing; Pu, Yunfeng; Fang, Jinggui; Shangguan, Lingfei (Frontiers in Plant Science, 2023)
Viticultural production is accompanied by many valuable by-products such as grapevine stem and seed, so grapevine has high edible, medicinal and industrial economic value. Drought is a common and serious abiotic stress in viticulture and it is urgent to select effective measures to alleviate it. As a new plant growth regulator, 5-aminolevulinic acid (ALA) has been applied more and more frequently in agriculture in recent years, which provided a novel idea for mitigating drought stress in viticulture. the leaves of ‘Shine Muscat’ (‘SM’) grapevine seedlings were treated with drought, drought plus 5-aminolevulinic acid (ALA, 50 mg/L) and normal watering, respectively, to clarify the regulatory network of ALA alleviating drought stress in grapevine. Physiological indicators showed that ALA could effectively reduce malondialdehyde (MDA) accumulation and increase the activities of peroxidase (POD) and superoxide dismutase (SOD) in grapevine leaves under drought stress. Furthermore, ALA reduces ABA by upregulating CYP707A1, thus relieve stomatal closure under drought. Chlorophyll metabolism pathway and photosynthetic system are the major pathways of ALA to alleviate drought. Changes in genes of chlorophyll synthesis including CHLH, CHLD, POR, and DVR, degradation related genes such as CLH, SGR, PPH and PAO, Rubisco related gene RCA, photorespiration related gene AGT1 and GDCSP form the basis of these pathways. In addition, antioxidant system and osmotic regulation play an important role in ALA to maintain cell homeostasis under drought. The reduction of glutathione, ascorbic acid and betaine after ALA application confirmed the alleviation of drought. In summary, this study revealed the response mechanism of grapevine to drought stress and the alleviating effect of ALA, providing a new idea for alleviating drought stress in grapevine.